PERSPEKTIF PERTOLONGAN PERSALINAN OLEH DUKUN BAYI DI DESA BUMIJAWA KECAMATAN BUMIJAWA KABUPATEN TEGAL TAHUN 2009 - Siswati; Siti Erniyati B.P; Kodijah ,SST (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
In Bumijawa village, Bumijawa, Tegal in 2009, the giving birth to health workers was only 63,1%, it is so far from the target of 90% in 2010. It shows that the role of  traditional birth attendans is still high. This  study is  aimed to  find information about  giving  birth  aid  by traditional birth attendans from  the  mother  and  traditional  birth  attendans  aspect  in  Bumijawa  village,  Tegal. The  research design used was qualitative approach. The population consists of two groups. The first group off all the  mothers  who gave birth  to  traditional birth attendans, and the  second  group are  all  traditional birth attendans who live in Bumijawa village, Bumijawa, Tegal. The data gathering technique used for  the  first  group  is  in  depht  interview,  and  for  the  second  group  is  Focus  Group  Discussion (FGD).The gathered data was examined with triangulation technique. The result of this study shows that  mothers  had  different  perception  about  giving  birth  aid  that  is  done  by  traditional  birth attendans. All of traditional birth attendans have same perception about the meaning of giving birth, the parturition term nursing and the system of reporting that is done by traditional birth attendans. It is  needed  a  controlling and  coaching  program for  active traditional  birth  attendans  continually  in order  to  get  the  scope  of  giving  birth  aid  target  by  health  worker  that  is  90%  in  2010  can  be reached.Key words  : Giving birth aid, traditional birth attendans